Adipose-derived mesenchymal stromal cells induce immunomodulatory macrophages which protect from experimental colitis and sepsis. Issue 8 (25th May 2012) - Anderson, Per; Souza-Moreira, Luciana; Morell, Maria; Caro, Marta; O'Valle, Francisco; Gonzalez-Rey, Elena; Delgado, Mario
Abstract : Objective: To investigate the effect of adipose-derived mesenchymal stromal cells (ASCs) on the activation state of macrophages (MΦ) in vitro, and the potential therapeutic effect of these cells in experimental colitis and sepsis. Design: Murine bone marrow-derived macrophages were cultured with ASCs or with ASC conditioned media (ASC-MΦ) and characterised for the expression of several regulatory macrophage markers, including enzymes and cytokines, and for their immunomodulatory capacity in vitro. The therapeutic effect was investigated of ASC-MΦ in two models of experimental inflammatory colitis induced by trinitrobenzene sulphonic acid and dextran sodium sulphate, and in polymicrobial sepsis induced by caecal ligation and puncture. Results: ASC-MΦ showed a phenotype that clearly differed from the classically activated macrophages or the alternatively activated macrophages induced by interleukin (IL)-4, characterised by high arginase activity, increased production of IL-10 upon restimulation and potent immunosuppressive activity on T cells and macrophages. Activation of cyclo-oxygenase-2 on ASCs seems to be critically involved in inducing this phenotype. Systemic infusion of ASC-MΦ inhibited colitis in mice, reducing mortality and weight loss while lowering the colonic and systemic levels of inflammatory cytokines. Importantly, therapeutic injection of ASC-MΦ in established chronic colitis alleviated its progression and avoided disease recurrence. Moreover, ASC-MΦ protected from severe sepsis by reducing the infiltration of inflammatory cells into various organs and by downregulating the production of several inflammatory mediators, where ASC-MΦ-derived IL-10 played a critical role. Conclusion: ASCs induce a distinct regulatory activation state of macrophages which possess potent immunomodulatory ability and therapeutic potential in inflammatory bowel diseases and sepsis.